In this post, we will cover , how we can convert cos sin inverse x and sin cos inverse x in the terms of x
Value of cos sin inverse x
f(x)=cossin−1x
Let θ=sin−1x
or sinθ=x
Now we know that θ∈[−π/2,π/2]
Also cos is positive in Ist and IV quadrant.
Therefore cosθ is positive. it will give by
cos \theta = \sqrt {1 – sin^2 \theta } =\sqrt {1 -x^2}
Therefore
f(x) =cos sin^{-1} x = \sqrt {1 -x^2}
Value of sin cos inverse x
f(x) =sin cos^{-1} x
Let \theta = cos^{-1} x
or cos \theta =x
Now we know that \theta \in [0, \pi]
Also sin is positive in Ist and II quadrant.
Therefore sin \theta is positive. it will give by
sin \theta = \sqrt {1 – cos^2 \theta } =\sqrt {1 -x^2}
Therefore
f(x) =sin cos^{-1} x = \sqrt {1 -x^2}
Summary
cos sin^{-1} x = sin cos ^{-1} x=\sqrt {1 -x^2}